2021
DOI: 10.1371/journal.pone.0254908
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput phenotyping to dissect genotypic differences in safflower for drought tolerance

Abstract: Drought is one of the most severe and unpredictable abiotic stresses, occurring at any growth stage and affecting crop yields worldwide. Therefore, it is essential to develop drought tolerant varieties to ensure sustainable crop production in an ever-changing climate. High-throughput digital phenotyping technologies in tandem with robust screening methods enable precise and faster selection of genotypes for breeding. To investigate the use of digital imaging to reliably phenotype for drought tolerance, a genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 76 publications
(110 reference statements)
1
14
0
Order By: Relevance
“…Drought is one of the most severe and unpredictable abiotic stresses, occurring at any growth stage and affecting crop yields [66]. It presents a substantial challenge to the sustainability of agriculture [67].…”
Section: Discussionmentioning
confidence: 99%
“…Drought is one of the most severe and unpredictable abiotic stresses, occurring at any growth stage and affecting crop yields [66]. It presents a substantial challenge to the sustainability of agriculture [67].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the genotype, IIHR 2195 showed its uniqueness through its response under water limiting conditions. Joshi et al (2021) shoot biomass was lower as compared to control. The reductions in fresh and dry weights of tomato plants are observed under deficit water stress (Ors et al, 2021) and studies have shown that tomato genotypes exhibit wide variability in drought tolerance (Conti et al, 2019).…”
Section: Resultsmentioning
confidence: 76%
“…Previous studies have suggested that plant seeds with the C4H mutation lead to a significant decrease in anthocyanins, growth hormones, and lignin in Arabidopsis [ 9 ]. Similarly, the abundance of C4H expression at the transcriptional level and protein level can significantly influence the biosynthesis of aromatic compounds and flavonoids in plants [ 10 , 11 ]. These findings have provided valuable insights towards the importance of C4H in plants that can affect the synthesis and accumulation of flavonoids and phenolic compounds by regulating its expression level along their biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Drought is considered as one of the most important factors affecting plant growth and yield, having a major impact on gene expression, morphology, metabolic adjustments, and photosynthetic modifications. Several studies have demonstrated that plant growth and development can be hampered by osmotic and oxidative stress, ion deficiencies, and metabolic disturbances when water is scarce [ 11 ]. Similarly, severe water deficiency has a significant negative impact on the growth and development of safflower [ 12 ].…”
Section: Introductionmentioning
confidence: 99%